2018
DOI: 10.1111/jfpe.12891
|View full text |Cite
|
Sign up to set email alerts
|

At‐line monitoring of industrial frying processes using ATR‐FTIR‐PLS method

Abstract: This study investigated the application of infrared spectroscopy with multivariate calibration methods for at‐line monitoring of the degradation of soybean oil in industrial frying processes by determining when the acidity index and total polar materials (TPM). The infrared spectra (650–3,200 cm−1) were acquired using the attenuated total reflection accessory (ATR‐FTIR), with a resolution of 4 cm−1, and 16 scans. Partial least‐squares regression (PLS) models were evaluated for individual and simultaneous deter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 36 publications
0
4
0
Order By: Relevance
“…Table 1 presents the variables of interest (IV), the number of bands (N) of the preprocessing MIR spectra, RMSEC, REMSECV, RMSEP, the number of latent variables (LV), calibration R 2 (R 2 cal ), cross-validation R 2 (R 2 val ), and the R 2 of prediction (R 2 pred ). In a study by Fetter et al [63], a quadratic cross-validation error was observed, with an average value of 1.6895 with 13 latent variables in the two models proposed to predict AI in frying oils. Pre-processing in the first model employed data normalization, 1D, and MC.…”
Section: Results Of Calibration and Prediction Through Plsrmentioning
confidence: 99%
“…Table 1 presents the variables of interest (IV), the number of bands (N) of the preprocessing MIR spectra, RMSEC, REMSECV, RMSEP, the number of latent variables (LV), calibration R 2 (R 2 cal ), cross-validation R 2 (R 2 val ), and the R 2 of prediction (R 2 pred ). In a study by Fetter et al [63], a quadratic cross-validation error was observed, with an average value of 1.6895 with 13 latent variables in the two models proposed to predict AI in frying oils. Pre-processing in the first model employed data normalization, 1D, and MC.…”
Section: Results Of Calibration and Prediction Through Plsrmentioning
confidence: 99%
“…Recently, Fetter et al. [ 37 ] also reported an ATR‐FTIR‐PLS method for determining TPCs in soybean oil used for industrial frying. They similarly optimized the model intervals with iPLS and synergy interval PLS (siPLS), finding that when spectral regions of 3200–2406, 2087–1929, 1769–1611, and 1133–975 cm −1 were used to build a TPC calibration model, the model performed best, with an RMSEP of 1.68 and an RMSEC of 0.74.…”
Section: Resultsmentioning
confidence: 99%
“…The most reliable way for the determination of stability and quality of frying oils during food preparation is the measurement of total polar matter (TPM). Those polar compounds are mainly dimers and polymers of triglycerides formed in oil at high temperatures [8]. The disposal of frying oil is recommended when the level of TPM reaches 24% (for US, Germany, and France) [9].…”
Section: Introductionmentioning
confidence: 99%